2003
DOI: 10.1207/s1532785xmep0501_2
|View full text |Cite
|
Sign up to set email alerts
|

I Saw It on the Radio: The Allocation of Attention to High-Imagery Radio Advertisements

Abstract: This study was conducted to explore how the level of imagery in a radioDo radio listeners "see" it on the radio? The Radio Advertising Bureau (RAB) seems to think so. Campaigns, sponsored by the RAB to encourage radio advertising by businesses, highlight the strength of radio to engage the imagination and get listeners to "see" a product in use during exposure to a radio MEDIA PSYCHOLOGY, 5,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 34 publications
3
25
0
1
Order By: Relevance
“…) conducted a more specific study by analyzing the acoustic features of music (pitch, intensity, and pace) to hypothesize brand personality and brand associations with the music used by Republican and Democrat parties in 2016 us elections. The evidence on the well-reported mental imaginary(Bolls, 2013;Bolls & Lang, 2003;Kosslyn, Ganis & Thompson, 2010;Miller & Marks, 1992;Paivio, 1986;Schwartz, 1999), formerly defined as soundscapes (Van Leeuwen, 1999) or paysage sonore(Schafer, 1979) supported this study. This study found that the candidate Trump was using music to build a strong brand personality of himself as a patriot whereas Clinton used music to associate the brand with some democrat values.A mental image is the capacity "to see with the eye of the mind, listen with the ear of the mind"(Kosslyn, et al., 2010, p. 3).…”
supporting
confidence: 73%
“…) conducted a more specific study by analyzing the acoustic features of music (pitch, intensity, and pace) to hypothesize brand personality and brand associations with the music used by Republican and Democrat parties in 2016 us elections. The evidence on the well-reported mental imaginary(Bolls, 2013;Bolls & Lang, 2003;Kosslyn, Ganis & Thompson, 2010;Miller & Marks, 1992;Paivio, 1986;Schwartz, 1999), formerly defined as soundscapes (Van Leeuwen, 1999) or paysage sonore(Schafer, 1979) supported this study. This study found that the candidate Trump was using music to build a strong brand personality of himself as a patriot whereas Clinton used music to associate the brand with some democrat values.A mental image is the capacity "to see with the eye of the mind, listen with the ear of the mind"(Kosslyn, et al., 2010, p. 3).…”
supporting
confidence: 73%
“…When a viewer is listening to radio, watching television, or viewing a movie, the pace at which events occur and are processed is controlled by the stimulus, not by the viewer. In addition, processing radio, television, or a movie requires a number of simultaneous mental tasks to process both the structure and the meaning (Bolls, 2002;Bolls & Lang, 2003;Lang, 2000;Lang, Zhou, Schwartz, Bolls, & Potter, 2000;R. F. Potter, 2000).…”
Section: Belief and Realism As Defaultmentioning
confidence: 99%
“…, 1993; Unnava et al. , 1996; Babin and Burns, 1997; Miller and Marks, 1997; Bolls and Lang, 2003). Moreover, high‐imagery stimuli can enhance consumer attitudes towards the brand directly (Burns et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, imagery has a significant impact on the attitudinal and behavioural responses of readers. High-imagery ad stimuli (compared with low-imagery ad stimuli) can generate more favourable attitudes towards the advertisements (Bone and Ellen, 1992;Burns et al, 1993;Unnava et al, 1996;Babin and Burns, 1997;Miller and Marks, 1997;Bolls and Lang, 2003). Moreover, high-imagery stimuli can enhance consumer attitudes towards the brand directly (Burns et al, 1993;Babin and Burns, 1997) or indirectly (Bone and Ellen, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%